The Effect of Jigsaw Type Cooperative Learning Strategy to Improve Students' Critical Thinking Patterns - Bunga Aprili; Chairunnisa Amelia (Journal of Elementary School Education, 2022)
The purpose of this study was to determine the effect of the jigsaw type cooperative learning strategy on students' thinking skills and to determine the thinking skills of sixth graders at SD Bina Taruna I. The type of research applied was quantitative research using the "One Group Pretest and Posttest" design (initial test and final test). ) which was held on January 25 – March 25, 2022 at SDS Bina Taruna 1 Medan Marelan FY2021/2022. The data collection instrument was carried out through an essay test with a total of 15 test questions. The results of this study can be concluded based on the t value, it is known that the t-test value is 60,586 > ttable 1,729. t table is taken from the t-distributed table with a significant level used is 5% or 0.05 there is an influence Jigsaw cooperative learning strategy to improve students' critical thinking patterns in class VI SDS Bina Taruna 1 Medan Marelan. This is obtained from the student's score before being given treatment (pretest) obtaining a score of 64 to 79 with an average score of 71.75 in the sufficient category. While the results (posttest) after implementing the cooperative learning strategy, it is known that the value obtained is 82 and the highest score is 100 with an average of 90.40 in the very good category. So that the hypothesis proposed in this study is accepted